2009
DOI: 10.1161/hypertensionaha.109.128827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renal Perfusion Pressure on Renal Medullary Hydrogen Peroxide and Nitric Oxide Production

Abstract: Abstract-Studies were designed to determine the effects of increases of renal perfusion pressure on the production of hydrogen peroxide (H 2 O 2 ) and NO 2 Ϫ ϩNO 3 Ϫ within the renal outer medulla. Sprague-Dawley rats were studied with either the renal capsule intact or removed to ascertain the contribution of changes of medullary blood flow and renal interstitial hydrostatic pressure on H 2 O 2 and NO 2 Ϫ ϩNO 3 Ϫ production. Responses to three 30-minute step changes of renal perfusion pressure (from Ϸ85 to Ϸ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…As pressures were increased in ϳ30-mmHg steps between 80 and 150 mmHg, significant increases in medullary interstitial H 2 O 2 concentrations were observed along with parallel increases in urinary excretion of H 2 O 2 ( Fig. 3A) (84). Since increases in medullary H 2 O 2 reduce Na ϩ excretion, these observations indicate that H 2 O 2 plays a modulatory role in reducing the steepness of the pressure-natriuresis relationship, serving to dampen the pressure-natriuresis response.…”
Section: ·ϫmentioning
confidence: 95%
“…As pressures were increased in ϳ30-mmHg steps between 80 and 150 mmHg, significant increases in medullary interstitial H 2 O 2 concentrations were observed along with parallel increases in urinary excretion of H 2 O 2 ( Fig. 3A) (84). Since increases in medullary H 2 O 2 reduce Na ϩ excretion, these observations indicate that H 2 O 2 plays a modulatory role in reducing the steepness of the pressure-natriuresis relationship, serving to dampen the pressure-natriuresis response.…”
Section: ·ϫmentioning
confidence: 95%
“…An elevation of renal perfusion pressure during hypertension may directly increase ROS production in the renal medulla, MBF and NaCl delivery to, and reabsorption by, the TAL (125). Jin et al (125) reported that a short-term increase of renal perfusion pressure enhanced the production of both NO and H 2 O 2 in the outer medulla of rats. The increased NO was attributed to the pressure-induced increase in MBF that enhanced vascular shear stress and to the increased H 2 O 2 with higher flow rates through the mTAL.…”
Section: Intrarenal Distribution Of Blood Flowmentioning
confidence: 99%
“…Urine and blood samples were collected during infusion experiments and Na + , K + , and creatinine levels were analyzed as previously described. 60,61 Figure 8. Chronic intravenous infusion of EGF prevents development of hypertension and kidney damage in SS rats fed a HS diet.…”
Section: Elisa Assay and Biochemical Analyses Of Electrolytesmentioning
confidence: 99%